Research in the central part of Severynivka hillfort (quadrats F80, F90, G71, G81) - Shelekhan, Oleksandr; Lifantii, Oksana; Boltryk, Yuriy; Ignaczak, Marcin (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2016)
The article deals with excavations in the central part of Severynivka hillfort. In the mentioned area there was found and studied a part of the large multi ‑layered complex, which is considered as the remains of probable public worship structure. in the complex filling there were revealed numerous finds of wares, including a number of complete ta ‑bleware and miniature forms, tools, jewelry and weapons. Also there were traced the tracks of rites administering that is recorded by the physical layout of objects in the complex and a female jaw find.
Ukrainian fortresses a study of a strongholds system from the early iron age in Podolia
Keywords: eastern European forest ‑steppe; Scythian period; hillfort; sanctuary; objects of worship; ritual practice; Early Iron Age